Species composition, stand structure, and carbon stock in the agroforestry system of Wana Lestari Community Forestry, West Nusa Tenggara, Indonesia - RAHMA DWI AKDAH; NURHENI WIJAYANTO; ADISTI PERMATASARI PUTRI HARTOYO (Society for Indonesian Biodiversity, 2024)
Abstract. Akdah RD, Wijayanto N, Hartoyo APP. 2024. Species composition, stand structure, and carbon stock in the agroforestry system of Wana Lestari Community Forestry, West Nusa Tenggara, Indonesia. Biodiversitas 25: 3350-3358. Climate change is characterized by shifting climate patterns that result in erratic weather phenomena. One of the major consequences of climate change is the reduction in biodiversity and the increased concentration of greenhouse gases (GHGs), primarily carbon. Agroforestry systems (AF) have emerged as a potential solution to mitigate these effects by conversing biodiversity and enhancing carbon stocks. This study aims to analyze the species composition and structure of tree stands and estimate the carbon stock in the AF of the community forest (HKm). The methods used employed included vegetation analysis, stand structure measurement using the Spatially Explicit Individual-based Forest Simulator (SExI-FS), and carbon stock estimation using allometric equations and destructive approaches for seedlings and understory levels. A total of 25 plots, each measuring 20×20 m, were used for data collection. The results show that the species composition in HKm Wana Lestari consists of 63 plant species from 40 families. The highest importance value index (IVI) was recorded for durian (Durio zibethinus Murray) at the pole growth level (90.34%), while coffee (Coffea robusta L.Linden) emerged as the dominant species within the agroforestry system. The diversity index (H') ranged from 0.40 to 2.29, indicating a medium category of diversity. The stand structure did not follow the expected